(untitled) (Semiárida, 2022)
Wheat is a cereal of great importance in human nutrition, so the quality assessment is proportional to production. You should not only think about the quantity of grains that are going to be produced but also about their ability to achieve quality flour with efficient use of resources. The objective of this work was to characterize environmental and management factors that determine the quality and productivity of wheat cultivation in the province of La Pampa. Two varieties of wheat belonging to two different quality groups (GC) (GC 1 and 2) were evaluated, in the coarse plain and in the medanous plain. The treatments were an unfertilized control, fertilization at sowing with two doses of nitrogen (N) (40 and 80 kg.ha-1), postponed (40 and 80 kg N.ha-1) and divided into sowing and tillering. At each site, an initial characterization of edapho-climatic variables was carried out. In tillering, heading and harvest maturity, edaphic humidity, nitrates in soil and total dry matter were determined. At maturity, the yield components and baking quality attributes were determined. No variety-site-management interaction was found. The 40S+40M and 80S treatments achieved the highest growth rate, therefore, more biomass and yield. Protein content had site-management interaction. Sites differentiated by their nutrient supply and edaphic quality have different N requirements to achieve 11% protein with the highest yield, and optimizing efficiency in the use of N. The higher N content increased the gluten content and W. The varieties did not present differences between them and their behavior was more influenced by their site than by the GC. The site and fertilization had a notable influence on productivity and the expression of quality. Director: Funaro, Daniel Oscar Co-director: Quiroga, Alberto Raúl